LncRNA HOTAIRM1 promotes osteogenesis by controlling JNK/AP‐1 signalling‐mediated RUNX2 expression. Issue 11 (11th September 2019) - Fu, Lei; Peng, Shifang; Wu, Wanfeng; Ouyang, Yi; Tan, Deming; Fu, Xiaoyu
Abstract: Mesenchymal stem cells (MSCs) have potential ability to differentiate into osteocytes in response to in vitro specific induction. However, the molecular basis underlying this biological process remains largely unclear. In this study, we identify lncRNA HOTAIRM1 as a critical regulator to promote osteogenesis of MSCs. Loss of HOTAIRM1 significantly inhibits the calcium deposition and alkaline phosphatase activity of MSCs. Mechanistically, we find that HOTAIRM1 positively modulates the activity of JNK and c‐Jun, both of which are widely accepted as crucial regulators of osteogenic differentiation. More importantly, c‐Jun is found to be functionally involved in the regulation of RUNX2 expression, a master transcription factor of osteogenesis. In detail, c‐Jun can help recruit the acetyltransferase p300 to RUNX2 promoter, facilitating acetylation of histone 3 at K27 site, therefore epigenetically activating RUNX2 gene transcription. In summary, this study highlights the functional importance of HOTAIRM1 in regulation of osteogenesis, and we characterize HOTAIRM1 as a promising molecular target for bone tissue repair and regeneration.